INDIVIDUAL PREDICTION OF THE DEVELOPMENT OF CERVICAL INTRAEPITHELIAL NEOPLASIA IN WOMEN TO MEDICAL AND SOCIAL RISK FACTORS - Kamilova, I.A (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: The study of medical and social risk factors for the development of cervical pathology and the development of models for predicting the likelihood of developing a disease in order to identify it in time and prescribe adequate therapeutic and preventive measures. Material and methods: The study was carried out as part of the research work of the Department of Obstetrics and Gynecology No. 2 of the Tashkent Medical Academy. The main group consisted of 226 patients with a clinically and cytologically confirmed diagnosis of CIN; the comparison group included 165 women without clinical signs of CIN. Results: Using the methods of mathematical statistics, the significance was studied and the leading medical and social risk factors were identified, based on which, using the logistic regression equation, a mathematical model was developed that allows predicting at an individual level the likelihood of developing cervical intraepithelial neoplasia. Testing results confirmed the effectiveness of the developed model. Conclusions: It is proposed to use the identified risk factors and the results of prognostic modeling when conducting preventive examinations in order to identify patients with a high risk of developing cervical pathology and prescribing preventive treatment and preventive measures to them.